Avaliação de dois consórcios públicos de saúde municipais no estado do Ceará - Lobo, Pryscila Gomes (2025)
The present research aims to evaluate the School Autonomy Program (PAE) in the public schools of the Maracanaú Municipal Network, in Ceará, Brazil. The program was created in 2006 by the Municipal Department of Education. Autonomy is a complex concept that has been constructed historically through relationships with various social, political, and self-interest spheres (Morin, 2014; Massaú & Karck, 2020; Coutrim, 2016; Santos, 2024). School autonomy,in particular, should be understood as a continuous process of negotiation and collective construction that responds to social demands for an education that prepares students not Only for the labor market but also for full citizenship (Lima, 2023; Mello, 2024; Muller, 2021). The PAE was established to decentralize municipal educational management by granting schools greater administrative and financial autonomy. It is grounded in Municipal Law No. 1.096 of 2006 and aligned with educational legislation, especially the National Education Guidelines and Framework Law (LDB) (Brazil, 1996). From a counter-hegemonic evaluation perspective, this study seeks to assess the PAE in Maracanaú through an in-depth evaluation framework that considers the content, context, trajectory, temporality, and territoriality of the policy (Rodrigues, 2008, 2016, 2011). The research adopts a qualitative approach (Minayo, 2017), and considering its objectives, it is characterized as exploratory and descriptive, using the multiple case study method as its strategy (Yin, 2015). Data collection will involve techniques such as document analysis and semi-structured interviews (Minayo; Deslandes; Gomes, 2009). The analysis of the collected data will be conducted through document analysis and discourse analysis (Orlandi, 2020), aiming to understand the processes that shape autonomy in the school context through the PAE. The evaluative research findings indicate that: (i) Although the program proposes decentralization, school autonomy is limited by bureaucratic barriers and dependency on the Department of Education; (ii) Institutional actors partially recognize the program's advances but reveal contradictions between theory and practice, express veiled critical perceptions, and point out inequalities in resource distribution and structural challenges that hinder equity among schools; (iii) School Councils stand out as key bodies in promoting democratic management and social oversight. Despite its limitations, the PAE has the potential to drive educational improvements by enabling investments and strengthening ties between schools and communities. However, its managerial model faces tensions with the real conditions of schools, demanding revisions to ensure the effectiveness and fairness of the educational policy.